ENKULTURASI BUDAYA UNSUR PETINGGI ADAT MINANGKABAU TALI TIGO SAPILIN DI SUMATERA BARAT - Ismail Ismail; Dahyul Daipon; Muhiddinur Kamal; Muhamad Rezi (PERADA, 2023)
As a tourist destination, West Sumatra will certainly interact directly with foreign cultures. This interaction has the potential to result in the emergence of changes and shrinkage of the pattern of traditional community life. This study examines the enculturation of Minangkabau customs by local leaders (Tali Tigo Sapilin). The problems in this research are, first, how is the process of cultural enculturation carried out by Tali Tigo Sapilin's leadership in West Sumatra? Second, what factors influenced Tali Tigo Sapilin's leadership in the enculturation process in West Sumatra? This study uses a qualitative approach by collecting data through observation, in-depth interviews, and documentation studies, as well as with Focus Group Discussions (FGD). The results of this research indicate that the inheritance of cultural values by Tali Tigo Sapilin's leadership is carried out through alek batagak penghulu, batamat kaji/Khatam Qur'an, Malapeh paga, and badoa bajamba. The factors that influence Tali Tigo Sapilin's leadership in the enculturation process in West Sumatra are the changing role of Tali Tigo Sapilin's leadership in Development, Changes in the Role of Ninik Mamak in Land Ownership.